Establishment and maintenance of leguminous living mulches for irrigated systems in the semi-arid West - Beahm, Andrew T., author; Brummer, Joe E., advisor; Pearson, Calvin H., committee member; Hansen, Neil C., committee member; Nissen, Scott J., committee member (Colorado State University. Libraries, 2011)
Management strategies for the establishment and maintenance of perennial leguminous living mulches were tested at irrigated sites in Colorado. Living mulches have been successfully integrated into corn (Zea mays) cropping systems in the upper Midwest of the United States. These studies focused on adapting the practice to irrigated environments in the semi-arid West through mulch and cash crop species selection and determination of appropriate suppression regimes. Different mulch/annual crop combinations were tested in both the establishment year and with previously established perennial legume stands. Spring herbicide regimes were tested on living mulches, and potential mulch species were screened for recovery from glyphosate [N-(phosphonomethyl)glycine] application. The goal of the first study was to determine whether birdsfoot trefoil (Lotus corniculatus), white clover (Trifolium repens), and a mix of white clover, red clover (Trifolium pretense), and kura clover (Trifolium ambiguum) could be co-established with corn and oats (Avena sativa) for use as living mulches. Legumes were seeded with annual crops at two irrigated sites. Mulch crops did not have any effect on annual crop yield or quality. Yields of legumes established with corn averaged 276 kg ha-1 in spring of the following year while legumes established with oats cut at the boot and soft dough stages yielded 951 and 611 kg ha-1, respectively. Among legume treatments, the clover mix yielded the highest, averaging 869 kg ha-1 across annual crops followed by birdsfoot trefoil and white clover at 542 and 427 kg ha-1, respectively. The second study tested different living mulch and annual crops for performance and compatibility. Corn and soybeans (Glycine max) were planted into established legume stands. Fertility treatments of 0, 84, 168, and 225 kg ha-1 nitrogen (N) were also applied to corn without a living mulch and used to generate N response curves to quantify N inputs of living mulches, which received only 84 kg N ha-1. Legume N contributions of living mulch treatments were 69, 46, 45, 32, and 23 kg ha-1 for alfalfa (Medicago sativa), white clover, birdsfoot trefoil, red clover, and a mix of birdsfoot trefoil/red clover, respectively, in corn silage. In corn grain, N contributions of legume treatments were 52, 43, 23, 20, and 18 kg ha-1 for white clover, alfalfa, birdsfoot trefoil/red clover mix, birdsfoot trefoil, and red clover, respectively. Soybean yields did not respond positively or negatively to the presence of living mulches. Birdsfoot trefoil had the greatest fall yield at 282 kg ha-1. The goal of the third study was to determine whether previously established birdsfoot trefoil, white clover, and a mix of white clover, red clover, and kura clover could be suppressed with paraquat (1,1'-dimethyl-4,4'-bipyridylium-dichloride) and glyphosate for use as living mulches in corn. Preplant treatments included: paraquat at 0.7 kg a.i. ha-1 and glyphosate at 1.0, 1.5, and 2.0 kg a.e. ha-1. All of these were followed by a mid-season application of glyphosate at 1.0 kg a.e. ha-1. Corn grain and legume yields were recorded in the fall. Legume by suppression treatment interactions occurred for both of these factors at the sprinkler irrigated site. At the furrow irrigated site, corn grain yields with birdsfoot trefoil averaged 11.2 Mg ha-1, which was greater than with white clover and the clover mix that yielded 10.1 and 10.0 Mg ha-1, respectively. Fall legume biomass yields of birdsfoot trefoil, white clover, and the clover mix were 11, 343, and 320 kg ha-1, respectively. Suppression treatment did not have any effect on grain yield or legume biomass. Even modest recovery of the clovers during the growing season resulted in some corn yield reduction. The fourth study evaluated persistence of legumes after glyphosate application by measuring biomass relative to an untreated control. Field tests included rates of 1.0, 1.5, 2.0, and 2.5 kg a.e. ha-1, while trials of potted plants started in the greenhouse lacked the 2.5 kg a.e. ha-1 rate. White clover had the greatest recovery relative to the control in the field trial, with no glyphosate rate effect by sixteen weeks after application. Alfalfa and birdsfoot trefoil consistently recovered less than red and white clovers. In the potted plant trial, above ground biomass of kura clover, white clover, birdsfoot trefoil, red clover, and alfalfa averaged 19, 7, 5, 2, and 1% of the control, respectively across rates. Preliminary results suggest that living mulch cropping systems may be a viable alternative under irrigation for producers in the western US. Mulch crops can be successfully co-established with corn or oats. White clover shows potential as a living mulch due to its positive effects on corn grain and silage yields when adequately suppressed. It also has high glyphosate tolerance. Leguminous living mulches can reduce nitrogen fertilizer needs, but adequately suppressing the mulch to minimize annual crop yield losses while maintaining the perennial legume stand remains a challenge.
Keywords: clover; living mulch; cover crop